Effects of both blended and pure biodiesel on waste heat recovery potentiality and exhaust emissions of a small CI (compression ignition) engine. (15th June 2015) - Magno, Agnese; Mancaruso, Ezio; Vaglieco, Bianca Maria
Abstract: The increasing spread of alternative fuels for compression ignition engines has required an improved knowledge of the energetic potentiality and the exhaust emissions of biodiesel. In this paper, energy and exergy analyses were performed to assess the energy distribution and to characterize the waste heat energy of a small compression ignition engine. The investigation was carried out on a three-cylinder, 1028 cm 3 engine equipped with a CR (common-rail) injection system. Gas emissions and particulate matter concentration were measured and particles were characterized in terms of number and size at exhaust. The engine was fuelled with commercial diesel fuel, a blend of 50% v/v rapeseed methyl ester (RME) and pure RME. Operating conditions at different engine speeds, at both medium and full load, were investigated. It was found out that the combustion efficiency is improved by biodiesel. A trade-off between the waste heat of the exhaust gas and the cooling water was observed. The quantity and quality of energy recovered by exhaust gas decreases as the content of biodiesel increases. A defined trend of the heat recovered from cooling water was not detected for the tested fuels. Lower exhaust emissions were measured when the engine was fuelled with both blended and pure RME with respect to diesel fuel. However, the analysis of the data has shown that a proper engine calibration could further optimize the combustion process and emission formation when the engine is fuelled with biodiesel. Highlights: Combustion efficiency is improved by biodiesel. A trade-off between the waste heat of the exhaust gas and cooling water was observed. The heat recovered by exhaust gas decreases as the content of biodiesel increases. Exhaust gas have higher exergy content than cooling water at full load conditions. Blended and pure RME emit lower exhaust emissions than diesel fuel.